Clinical Investigations of CAR-T Cell Therapy for Solid Tumors - Chen, Kun; Wang, Shuhang; Qi, Dan; Ma, Peiwen; Fang, Yuan; Jiang, Ning; Wu, Erxi; Li, Ning (Frontiers in Immunology, 2022)
Cell therapy is a distinguished targeted immunotherapy with the potential and limitless imagination to treat solid tumors in the new era for cancer treatment. Cell therapy products include genetically engineered cell products and non-genetically engineered cell products. Several recent cell therapies, especially chimeric antigen receptor (CAR) -T cell therapies have been approved as novel treatment strategies for cancer. Many clinical trials on cell therapies, in the form of cell therapy alone or in combination with other treatments, in solid tumors, have been conducted or ongoing. However, there are still challenges since adverse events and limited efficacy of cell therapies have also been observed. Here, we concisely summarize the clinical milestones of the conducted and ongoing clinical trials of cell therapy, introduce the evolution of CARs, discuss challenges and limitations for these therapeutic modalities, taking CAR-T as a main focus, and analyze disparities in the regulatory policies in different countries.